2007
DOI: 10.3746/jfn.2007.12.3.185
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Strawberry Puree on the Physicochemical Properties of Kochujang

Abstract: Quality characteristics of kochujang prepared with strawberry puree (10, 20, and 30% on the total weight basis) were investigated after 30 and 300 days of storage. The moisture content of strawberry kochujang at 300 days was considerably higher than that of strawberry kochujang at 30 days and increasing strawberry content from 0 to 30% significantly increased moisture content of kochujang progressively (p<0.05). Water activity and titratable acidity also showed similar trends, but pH showed the reverse trend w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
5
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
3
5
0
1
Order By: Relevance
“…The positive coefficient of the first order term of x 1 in Table 4 indicated that moisture content increased with increases in the strawberry puree content. Similar results were reported previously (17). In addition, the negative coefficient of the first order term of x 2 indicated that moisture content decreased with increases in the red pepper powder content.…”
Section: Effects On Moisture Content and Water Activitysupporting
confidence: 90%
See 3 more Smart Citations
“…The positive coefficient of the first order term of x 1 in Table 4 indicated that moisture content increased with increases in the strawberry puree content. Similar results were reported previously (17). In addition, the negative coefficient of the first order term of x 2 indicated that moisture content decreased with increases in the red pepper powder content.…”
Section: Effects On Moisture Content and Water Activitysupporting
confidence: 90%
“…3). A similar effect of strawberry puree content on the water activity of Kochujang was reported by others (17).…”
Section: Effects On Moisture Content and Water Activitysupporting
confidence: 87%
See 2 more Smart Citations
“…. 이에 따라 구기자의 좋은 성분을 이용하여 식품으로 서 이용하고자 전통차 (15), 구기자맥주 (16), 구기자분말을 이용한 생면 (17), 구기자고추장 (18), 구기자요쿠르트 (19), 구 기자인절미 (20), 쿠키 (21), 구기자전통주 (22) PRGSL-1, -2, -3, -4 and -5: 20, 40, 60, 80 and 100% of sugar added in parboiled raw Gugija fruit.…”
unclassified